MENYINGKAP HUBUNGAN AGAMA DAN FILSAFAT: MERENDA KESESATAN FILSAFAT AL-GHAZALI, MERESPONS KETERHUBUNGAN FILSAFAT DAN AGAMA IBNU RUSYD - Mas'udi, Mas'udi (LP2M IAIN kUDUS, 2013)
THE RELATIONSHIP BETWEEN RELIGION AND PHILOSOPHY (Searching the Fallacy Philosophy of al-Ghazali, Responding the Connection between Philosophy and Religion of Ibn Rushd). Philosophy and religion are considered as the two entities as if different. Religion is indicated on revelation as the primary foundation and affiliated to the principles of normativity. Meanwhile, the philosophy is more leaning on the principles of rationality embodies the values of divinity rububiyyah in the historical domain. Necessarily, the two aspects above adhere to the principles of various viewpoints. From these points, both of them want to achieve the ultimate truth in interpreting the texts of the Lord that is still abstract. Textuality and contextuality become the important determinants ultimately carried by the two segments of thought. The originality of religious doctrine becomes an important aspect which was presented by al-Ghazali in order to confront the world of philosophy-laden fiction. Philosophy and religion in the view of al-Ghazali are the two different entities and existences. Meanwhile, Ibn Rushd struggled to establish the two entities and the existences of this ijtihad which become an aspect that can be integrated. Both are struggling to find the truth.keywords: Philosophy, Religion, Theology, Logic, Confusion,.Filsafat dan agama dinilai sebagai dua entitas yang “seakan-akan” berbeda. Agama lebih berindikasi pada wahyu sebagai landasan primernya dan berafiliasi pada prinsip-prinsip normativitas. Sementara itu, filsafat yang lebih berhaluan pada prinsip-prinsip rasionalitas mewujudkan nilai-nilai ketuhanan rububiyyah dalam domain historis. Secara niscaya, kedua aspek di atas menganut prinsip-prinsip sudut pandang angle yang bervariasi. Dari variasi sudut pandang keduanya ingin mencapai suatu kebenaran hakiki dalam menafsirkan teks-teks Tuhan yang masih bersifat absrak. Tekstualitas dan kontekstualitas menjadi dua determinasi penting yang akhirnya diusung oleh kedua segmentasi pemikiran tersebut. Pengusungan orisinalitas doktrin agama menjadi aspek penting yang diketengahkan al-Ghazali guna mengkonfrontasi dunia filsafat yang sarat rekaan. Filsafat dan agama dalam pandangan al-Ghazali merupakan dua entitas dan eksistensi yang berbeda. Sementara itu, Ibnu Rusyd berjuang untuk mengukuhkan bahwa kedua entitas dan eksistensi ijtihad ini merupakan aspek yang dapat dipadukan. Keduanya berjuang untuk mencari suatu kebenaran.kata kunci: Filsafat, Agama, Teologi, Logika, Kerancuan, Hukum, Fikih.